Pengembangan Bahan Ajar Lembar Kerja Siswa (LKS) dalam Bentuk Brosur untuk Pembelajaran IPA di SMP ditinjau dari Aspek Kegrafikaannya - Myco Hersandi; I Ketut Mahardika; Nuriman Nuriman (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2017)
IPA brochures integrated as teaching SMP materials in terms of aspects grafika. The purpose of the study is to describe grafika (keproporsionalan font size, variety and ease of letters, the attractiveness of the color and placement of the layout) on the integrated IPA brochures teaching materials. This paper is the result of a study conducted through literature review and relevant literature for later in the descriptive analysis so as to obtain the appropriate standard grafika in developing an Integrated IPA teaching materials. From the results of the study it can be concluded that grafika includes keproporsionalan font size used should be balanced between the elements of the layout (title, author, illustrations, logos, etc.) and the size of the layout elements (typography, illustrations and supporting elements such as squares, circles and other decorative elements ) in proportion to the size of the teaching materials. Variations and Ease of letters used to read that is using two types of letters to be more communicative in conveying the information submitted. The attractiveness and harmony of the colors used must conform to the shape, color and size of the object so as to avoid any interpretation or understanding of learners. Placement layout like title, subtitle, text, and images are placed in accordance with a predetermined pattern so as to avoid misinterpretation of the material presented Keywords: LKS, brosur IPA terpadu, kegrafikaan